Kako je kuža Rik polepšal bibliopedagoške ure z otroki in mladostniki s posebnimi potrebami v Občinski knjižnici Jesenice - Jamar, Nina (Šolska knjižnica, 2012)
The article presents the cooperation between the Municipal library Jesenice and Elementary school Polde Stražišar for children with special needs. The cooperation started in the school year 2008/2009 with two departments of special program and in the next year another department joined. The aim of biblio-pedagogical lessons in Municipal Library Jesenice is to improve reading, speaking and writing skills of children and adolescents from Elementary school Polde Stražišar. The element of socialization is also included. Sometimes, the therapeutic dog Rik and his guide also help with reading.
Keywords: bibliopedagoške ure; branje; osnovne šole; otroci s posebnimi potrebami; pravljice; splošne knjižnice